Synergistic Interactions between Christia vespertilionis Leaves Extract and Chemotherapy Drug Cyclophosphamide on WRL-68 Cell Line - Abd Latip, Normala; Abd Mutalib, Nurliana (Asian Journal of Pharmaceutical Research and Development, 2019)
Christia vespertilionis locally known as ‘rerama’ has gained much attention as herbal preparation to treat various ailments and diseases although there is no conclusive evidence of its therapeutic values. Self-medication is commonly practiced by patients, underpinned by health believes that affect their adherence to medication regimens, and impacting on treatment outcomes. Therefore, in this study the phytochemical profile and potential interaction of this plant extracts with conventional chemotherapy drug cyclophosphamide were investigated. Water decoction and maceration method with 70% ethanol were used to extract the plant leaves. Phytochemical profiling of the extracts and compound identification was done using HPLC. Isoorientin was identified as the major phytochemical component of the extracts. MTT assay was used to screen cytotoxicity of the extract towards CRL2522, HaCaT, HepG2, MCF-7 and WRL68 cell lines. Combination index (CI) and isobologram were derived from combination treatment of extract and cyclophosphamide. Ethanolic extract has low cytotoxicity against all cell lines (IC50>1mg/mL). However, combination treatment of ethanolic extract and cyclophosphamide at IC15 and IC25 concentration resulted in synergism (CI<1). There is potential synergism arise with combination treatment of this plant with cyclophosphamide, which enhances cytotoxicity and the mechanism of synergism worth to be further investigated.